Improved Method for Imparting Porosity in Mesoporous Silica and its Applicability as Slow-release Carrier: Imparting Porosity in Mesoporous Silica - Vakkanti, Venkata Sridevi; Guntuku, Girija Sankar (Iranian Journal of Pharmaceutical Sciences, 2024)
Removing polyethylene oxide and polypropylene oxide co-polymer template to generate porosity is critical in synthesizing SBA 15 (MSN). Porosity generation among silica nanoparticles is in high demand due to its wide applications. Different physical treatments like calcination, solvent extraction ultrasonication, and a combination of methods were implemented to remove organic templates from pores. The particles obtained were characterized using FTIR to expose silanol functional groups. The PSL-5 particles were obtained via combination treatment, which was economical and was selected to formulate mosquito repellent cream. The optimized cream formulation with and without an MSN carrier was evaluated for mosquito repellency using diurnal mosquitoes and blank active citronellol using the arm cage method. The uniformity of particle size distribution and hexagonal porosity represented by crystallinity were evident from the SEM and XRD data. The zeta potential of -16.8 mv of SBA 15 indicates the stability of the particles. Comparison of FTIR of carrier SBA 15 and citronellol shows no incompatibility. The mesoporous material effectively deters mosquitoes for more than 3 hours. The novel template removal process utilizes mild temperature and a less solvent ratio of 1:3. Thus, the obtained MSN material showed prolonged mosquito repellency in the laboratory assay.